The importance of healthy and sustainable built environments for vulnerable groups of population / Bhzad Sidawi and Mohamed Taha Al-Hariri - Sidawi, Bhzad; Al-Hariri, Mohamed Taha (Faculty of Architecture, Planning & Surveying, 2015)
Research worldwide have demonstrated the adeverse impact unsustainabale and unhealthy built environment on citizens. In the case diabetes, studies have concentrated on the environmental impact and accessibility issues of a place i.e. the home and neighbourhood, whereas very few studies have addressed the spatial arrangement of places and linked it with the prevalence of diabetes. Also, little research has tackled the place's impact on diabetic patients and their views concerning their neighbourhoods. This paper illustrates the outcomes of survey that was carried out on diabetic individuals in the eastern province, Kingdom of Saudi Arabia (KSA). The paper makes recommendations on how to improve the built environment in the KSA to be sustainable and healthier for all citizens including the diabetic patients.